(untitled) (CAHIERS MAGELLANES-NS, 2024)
Work-life balance is the maintenance of a balance between responsibilities at work and at home. In recent years, the concept has become increasingly significant, particularly among women teachers in higher secondary schools. This article explores the work-life balance of women teachers in Sivagangai District, where work and family spheres often become antagonistic, each demanding substantial energy and time, leading to work-family conflict (WFC). These conflicts are further intensified by the cultural contradictions of motherhood, where women are encouraged to pursue fulfilling careers while also facing pressures to provide intensive parenting. Employed women often encounter challenges in finding adequate and affordable child and elderly care, contributing to work-life imbalance and role conflict. This study aims to examine the ability of women teachers to manage the multifaceted demands of their professional and personal lives. It recognizes that work-life balance is not merely about equally dividing time between work and non-work roles but involves a more complex interplay of various components. Through a case study approach, this research sheds light on the unique challenges faced by women teachers in Sivagangai District, providing insights into how they navigate and negotiate their work and family responsibilities. The findings of this study contribute to the broader understanding of work-life balance and offer potential strategies for improving the well-being of women teachers in similar contexts.